PENERAPAN KAIDAH FIQHIYAH DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH DI INDONESIA - Nisrina Zahrani Zahirah; Cantika Aqilla Ghani; Mashwa Elfa; Davina Fathiya Wulandari Putri Martono; Baidhowi Baidhowi (CV. Denasya Smart Publisher, 2025)
The development of Islamic economics in Indonesia has shown significant growth, in line with the increasing demand for a financial system based on sharia principles. However, this growth has also led to more complex disputes among business actors and Islamic financial institutions. In this context, the application of fiqhiyyah principles (legal maxims) plays a crucial role as a normative and methodological foundation in resolving Islamic economic disputes. This article aims to analyze how fiqhiyyah principles are applied in dispute resolution practices within both religious courts and alternative institutions such as sharia arbitration. The research employs a normative juridical method with conceptual and statutory approaches, supported by a review of relevant decisions from religious courts. The findings indicate that the application of fiqhiyyah principles—such as al-yaqīn lā yazūlu bi al-syak (certainty is not removed by doubt), al-‘ādah muhakkamah (custom is an authoritative source of law), and al-masyaqqah tajlib al-taysīr (hardship brings about ease)—serves as a key judicial consideration in realizing substantive justice aligned with maqāṣid al-syarī‘ah (the objectives of Islamic law). Therefore, the implementation of fiqhiyyah principles not only strengthens the legitimacy of Islamic law within the national legal system but also becomes an essential instrument for achieving equitable, beneficial, and socially just resolutions in Islamic economic disputes.